Effect of resveratrol and Regrapex-R-forte on Trichosporon cutaneum biofilm - Paldrychová, Martina; Kolouchová, Irena; Vaňková, Eva; Maťátková, Olga; Šmidrkal, Jan; Krmela, Aleš; Schulzová, Věra; Hajšlová, Jana; Masák, Jan (Folia microbiologica, 2019)
Microorganisms that cause chronic infections exist predominantly as surface-attached stable communities known as biofilms. Microbial cells in biofilms are highly resistant to conventional antibiotics and other forms of antimicrobial treatment; therefore, modern medicine tries to develop new drugs that exhibit anti-biofilm activity. We investigated the influence of a plant polyphenolic compound resveratrol (representative of the stilbene family) on the opportunistic pathogen Trichosporon cutaneum. Besides the influence on the planktonic cells of T. cutaneum, the ability to inhibit biofilm formation and to eradicate mature biofilm was studied. We have tested resveratrol as pure compound, as well as resveratrol in complex plant extract-the commercially available dietary supplement Regrapex-R-forte, which contains the extract of Vitis vinifera grape and extract of Polygonum cuspidatum root. Regrapex-R-forte is rich in stilbenes and other biologically active substances. Light microscopy imaging, confocal microscopy, and crystal violet staining were used to quantify and visualize the biofilm. The metabolic activity of biofilm-forming cells was studied by the tetrazolium salt assay. Amphotericin B had higher activity against planktonic cells; however, resveratrol and Regrapex-R-forte showed anti-biofilm effects, both in inhibition of biofilm formation and in the eradication of mature biofilm. The minimum biofilm eradicating concentration (MBEC80) for Regrapex-R-forte was found to be 2222 mg/L (in which resveratrol concentration is 200 mg/L). These methods demonstrated that Regrapex-R-forte can be employed as an anti-biofilm agent, as it has similar effect as amphotericin B (MBEC80 = 700 mg/L), which is routinely used in clinical practice.
Keywords: Amphotericin B; Antifungal Agents; mikrobiální testy citlivosti; Resveratrol; amfotericin B; rostlinné extrakty; Trichosporon; Stilbene; resveratrol; Anti-biofilm activity; Plant extract; Microbial Sensitivity Tests; Plant Extracts; Fallopia japonica; Reynoutria japonica; biofilmy; Vitis; antifungální látky; Biofilms